"n Ou-Testamentiese perspektief op sinkretisme: Die aanbidding van die "God van die voorvaders" as gevallestudie 1 - Beyers, Jaco (HTS teologiese studies, 2002)
An Old Testament perspective on syncretism: The belief in the “God of the forefathers” as case studyAlthough the term syncretism does not appear in the Old Testament, syncretism is widely seen as the process resulting from the contact of religions. All forms of cultural and religious contact can however not be identified as syncretism. Some forms of contact between religions are nothing more than the normal way in which religions were formed over the centuries. The way in which the belief in the “God of the forefathers” developed in the Old Testament serves as a case study to indicate how contact between religions can lead to the formation of a legitimate religion.